Melacak Akar Pondasi Hubungan Indonesia-Rusia Kajian Historis Menggali Motif-Motif Teologis, Nautis, ideologis, dan Politik pada Literatur Rusia Abad 11-20 - Jamaluddin Z, Wan (Buletin Al-Turas, 2005)
Nusantara image has entered the history of old Russian literature since the 11th-20th century. Its transmission process is in two ways. Firstly, translating classic and western European literature. Secondly, visiting Nusantara. This transmission effects the evolution of the Nusantara image in Russian literature representing the connection between two nations. This Nusantara image begins from the unrecognized Nusantara, a new age of translation, and a silverÂ age if translation.